(untitled) (Terr@ Plural, 2022)
This paper presents an analysis of the evolution of deaths caused by the COVID-19 pandemic in the municipality of Chapecó, State of Santa Catarina (Brazil). This is an ecological study, carried out through temporal analyzes using secondary data, which considers the number of deaths and the municipality’s health resources, from January 1st to July 31st, 2021. In this period, 562 deaths were registered of people with a confirmed diagnosis for COVID-19, of which 469 occurred between February and April. The profiles of such deaths were identified by sex and age group of each case. Overcrowding of beds was identified in the Intensive Care Units (ICUs), both in the Unified Health System (SUS) and in the private hospital network, especially in March, April, and May. Finally, it is highlighting the importance of vaccination to reduce mortality from the disease in the municipality.